MuSK: a new target for lethal fetal akinesia deformation sequence (FADS). Issue 3 (22nd January 2015) - Wilbe, Maria; Ekvall, Sara; Eurenius, Karin; Ericson, Katharina; Casar-Borota, Olivera; Klar, Joakim; Dahl, Niklas; Ameur, Adam; Annerén, Göran; Bondeson, Marie-Louise
Abstract : Background: Fetal akinesia deformation sequence syndrome (FADS, OMIM 208150) is characterised by decreased fetal movement (fetal akinesia) as well as intrauterine growth restriction, arthrogryposis, and developmental anomalies (eg, cystic hygroma, pulmonary hypoplasia, cleft palate, and cryptorchidism). Mutations in components of the acetylcholine receptor (AChR) pathway have previously been associated with FADS. Methods and results: We report on a family with recurrent fetal loss, where the parents had five affected fetuses/children with FADS and one healthy child. The fetuses displayed no fetal movements from the gestational age of 17 weeks, extended knee joints, flexed hips and elbows, and clenched hands. Whole exome sequencing of one affected fetus and the parents was performed. A novel homozygous frameshift mutation was identified in muscle, skeletal receptor tyrosine kinase ( MuSK ), c.40dupA, which segregated with FADS in the family. Haplotype analysis revealed a conserved haplotype block suggesting a founder mutation. MuSK (muscle-specific tyrosine kinase receptor), a component of the AChR pathway, is a main regulator of neuromuscular junction formation and maintenance. Missense mutations in MuSK have previously been reported to cause congenital myasthenic syndrome (CMS) associated with AChR deficiency. Conclusions: To our knowledge, this is the first report showing that a mutation in MuSK is associated with FADS. The results support previous findings that CMS and/or FADS are caused by complete or severe functional disruption of components located in the AChR pathway. We propose that whereas milder mutations of MuSK will cause a CMS phenotype, a complete loss is lethal and will cause FADS.